1993
DOI: 10.1177/104063879300500329
|View full text |Cite
|
Sign up to set email alerts
|

Botryoid Rhabdomyosarcoma of the Urinary Bladder in a Filly

Abstract: Neoplasia of the equine urinary bladder is seldom reported in the literature and is considered uncommon.2,7 Clinical cases are rarely described, and those reported often involve slaughterhouse studies. Of those tumors of the urinary bladder reported, most occurred in aged mares, although aged geldings were also affected. 2,7,9 Benign tumors of the urinary bladder include papillomas, adenomas, fibromas, leiomyomas, angiomas, and fibroepithelial polyps. 9,10 There are several reports of malignant tumors; however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 4 publications
0
24
0
Order By: Relevance
“…Loss of appetite and weight and pleural effusion were found in a 3 years old gelding (49 Two cases of embryonal botryoid rhabdomyosarcoma were reported to occur in young horses (63,65). A yearling filly was treated by ovariectomy for a large uterine tumour (18 kg!).…”
Section: Embryonic Hepatoblastomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of appetite and weight and pleural effusion were found in a 3 years old gelding (49 Two cases of embryonal botryoid rhabdomyosarcoma were reported to occur in young horses (63,65). A yearling filly was treated by ovariectomy for a large uterine tumour (18 kg!).…”
Section: Embryonic Hepatoblastomasmentioning
confidence: 99%
“…A large mass protruding into the vagina was debulked in a 2 years old filly (65). At necropsy three months later a large tumour (10x6x3 cm.)…”
Section: Embryonic Hepatoblastomasmentioning
confidence: 99%
“…Failed attempts to surgically excise a rhabdomyosarcoma and a SCC have also been previously described (Turnquist et al . ; Gandini et al . ).…”
Section: Introductionmentioning
confidence: 94%
“…Whilst transitional cell carcinoma (TCC) is the most frequently reported primary bladder neoplasm in the dog (Mutsaers et al 2003) and man (Johansson and Cohen 1997), it has rarely been reported in the horse with only 5 previously published cases (Traub et al 1983;Fischer et al 1985;Servantie et al 1986;Turner et al 1995;Patterson-Kane et al 2000). Other reports of neoplasia of the horse bladder include lymphosarcoma, leiomyosarcoma, fibromatous polyp and rhabdomyosarcoma (Sweeney et al 1991;Turnquist et al 1993;Hurcombe et al 2008; Barrell and Hendrickson 2009;Waldridge 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported to occur most commonly in the urinary bladder of large-breed dogs aged less than 2 years and has also been reported to occur in the urinary bladder of a smallbreed dog (Maltese) and a horse. 7,9 There is only one report of its occurrence in an organ other than the urinary bladder, i.e., in the uterus of a horse. 8 In this article, we describe the histopathology of botryoid rhabdomyosarcoma of the vagina in dogs.…”
mentioning
confidence: 99%